Sistemas de polinización en granadilla (Passiflora ligularis Juss.) como base para estudios genéticos y de conservación - Arias Suárez, Juan Carlos; Ocampo, John; Urrea Gómez, Ramiro (Universidad Nacional de Colombia, 2016)
The sweet granadilla (*P. ligularis* Juss.) is one of the main fruit species of tropical Andean region for its pleasant taste and nutritional content. Despite its importance, there is little information related pollination systems for determining genetic compatibility species. For this reason, this study aims to establish the effectiveness of natural pollinators and set the percentage of self-pollination for breeding. The study was carried out in the Tesorito farm (Manizales, Caldas) to 2,340 masl (17°C, RH 78%, BS 1,215 hours/year and rainfall 1,800 mm/year). The effectiveness of natural and assisted pollination was evaluated in 42 accessions of sweet passion fruit coming from 10 Colombian departments by using five treatments. Anthesis begin at 3:00 hours and finish at 5:00 hours, being more active during the last 60 minutes (70%). The sweet passion fruit can reach up 34.3% of set fruit by spontaneous self-pollination; however, the intervention of an animated vector significantly increased the set fruit (70%). The precipitation was the only variable that presented a high correlation in all the pollination treatments (r= -0.70), demonstrating its negative effect on them. Together these results suggest that P. ligularis is self-fertile specie, but depends on the pollinator agents for the genetic flow and the productivity. Further, natural pollinators should be preserved and integrated into crop management plans because they provide a reproductive service and ecosystem.